PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (STUDI KASUS PUSKESMAS RENDANG KARANGASEM): Pengaruh Motivasi Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan (Studi Kasus Puskesmas Rendang Karangasem) - Ratih mahacakri I Gusti Agung Istri Ratih Mahacakri Laksmi; Ni Wayan Ari Sudiartini (TALI JAGAD JOURNAL, 2023)
This study aims to obtain a tested qualitative explanation of the influence of motivation and leadership style on employee performance at the Rendang Karangasem Health Center. The research design used in this study is a qualitative research design. The type of data used is primary data and collected by in-depth interview method. The subjects of this study were all employees of the Rendang Karangasem Health Center, totaling 32 people, so this research was included in the population research category. Motivation and Leadership style have a positive influence and help the performance of Rendering Health Center employees to be better.